Revelation - Wall, Robert W. (Michigan Baker Books, 1991)
Horsemen, signs, seals, weeks{u2014}this volume in Hendrickson's popular New International Biblical Commentary tackles the New Testament book that puzzles and intrigues laypeople and students alike. Wall takes a sane, common-sense approach to Revelation
Keywords: Bible. -- Revelation -- Commentaries. Bible. -- Revelation. -- New International. -- Commentaries. Bible. -- New Testament. -- Apocalypse -- Commentaires. Bible. -- Revelation. Openbaring van Johannes (bijbelboek) Christianity -- Scriptures